Examining the Effect of Job Burnout on Organizational Conflict With The Mediation of Job Commitment - Wasan Kamil Afloog (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The objective of this investigation is burnout of occupation on organizational contradiction with the mediation of occupation commitment (case study: Al Muthani Cement Coefficienty). The investigation manner is applied in Conditions of objective and descriptive and survey in Conditions of conducting manner. The statistical society includes all the superintendrs and occupationholders in Al Muthani cement coefficienty, whose number is approximately 500 people, and in instruction to characterize the sample size, Cochran's formula was utilizated, and 217 people were randomly scaled. The manner of collecting inestablishment was a questionnaire, and to scale occupation exhaustion, Maslach (Mezlaj-Mezlach-Maslach) questionnaire (1981), Robbins' organizational contradiction (1994) and occupation occupation commitment was utilizated aboard Shaufli et al.'s (2001) questionnaire. After compiling the initial frameact, coefficient analysis was done to obtain the accuracy of the structure. Cronbach's alpha coefficient was utilizated to scale the relicapability of the questionnaire. Then, all the proposed hypotheses were tested and analyzed using the structural equation figureing technique and using smart pls software, and the findings showed that occupation exhaustion has a remarkable on burnout organizational contradiction with the mediation of occupation commitment in al-Muthani cement coefficienty.